2011
DOI: 10.1007/s10533-011-9631-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability in nutrient concentration and biofilm nutrient limitation in an urban watershed

Abstract: Nutrient enrichment threatens river ecosystem health in urban watersheds, but the influence of urbanization on spatial variation in nutrient concentrations and nutrient limitation of biofilm activity are infrequently measured simultaneously. In summer 2009, we used synoptic sampling to measure spatial patterns of nitrate (NO 3 -), ammonium (NH 4 ? ), and soluble reactive phosphorus (SRP) concentration, flux, and instantaneous yield throughout the Bronx River watershed within New York City and adjacent suburbs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 53 publications
1
24
1
Order By: Relevance
“…These findings are consistent with the urban stream syndrome and urban watershed concepts in that greater impervious surface leads to less infiltration, greater stormwater runoff, and higher nutrient concentrations flowing through the watershed (Walsh et al 2005;Kaushal & Belt 2012). Hoellein et al (2011) found a strong relationship between NO 3 ¡ ÀN instantaneous yield and percent impervious surface, while others found relationships between stream water NO 3 ¡ ÀN, a predictor of denitrification rates, and land use (Arango & Tank 2008). In contrast to our findings, Meyer et al (2005) found that NO 3 ¡ ÀN decreased with increasing urbanization.…”
Section: Discussionsupporting
confidence: 79%
“…These findings are consistent with the urban stream syndrome and urban watershed concepts in that greater impervious surface leads to less infiltration, greater stormwater runoff, and higher nutrient concentrations flowing through the watershed (Walsh et al 2005;Kaushal & Belt 2012). Hoellein et al (2011) found a strong relationship between NO 3 ¡ ÀN instantaneous yield and percent impervious surface, while others found relationships between stream water NO 3 ¡ ÀN, a predictor of denitrification rates, and land use (Arango & Tank 2008). In contrast to our findings, Meyer et al (2005) found that NO 3 ¡ ÀN decreased with increasing urbanization.…”
Section: Discussionsupporting
confidence: 79%
“…NH + 4 -N was the dominant form of TDN except at the Headwater and Estuary sites where NO − 2 + NO − 3 -N was predominant (Table 1). This finding differs from urban watershed studies in Japan and the USA, where elevated NO − 3 -N concentrations in stream water was the dominant response to urbanization (Wollheim et al 2005;Rosenzweig et al 2008;Ileva et al 2009;Hoellein et al 2011). However, the concentrations of NO − 2 + NO − 3 -N that we observed (Table 1) were in a similar range as the urbanized Baltimore watersheds, approximately 0-3 mg N L −1 (Kaushal et al 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…Wollheim et al (2005) compared an urban catchment (79% urban) with a forested catchment (16% urban) and found that the urban catchment exported approximately 45% more NO − 3 -N in stream water. In the highly urbanized New York City metropolitan area, instantaneous NO − 3 -N yield was significantly correlated with impervious surface cover (%) in sub-watersheds of the Bronx River watershed (Hoellein et al 2011). The highest NO − 3 -N concentrations were delayed from the instream flow peak during rain events in a New Jersey urban catchment (Rosenzweig et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…run-off) inputs (Walsh et al, 2005). Johnson, Tank & Dodds, 2009;Hoellein, Arango & Zak, 2011). Differential enrichment of N and P may also change the identity of limiting nutrients with increasing urbanisation.…”
Section: Introductionmentioning
confidence: 99%